Pengaruh Financial Leverage, Kebijakan Dividen, Profitabilitas, Ukuran Perusahaan Dan Likuiditas Terhadap Nilai Perusahaan Pada Perusahaan Farmasi Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2015-2019 - M. Oksa Ariandi; Leriza Desitama Anggraini; Reny Aziatul Pebriani (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
This study aims to examine and determine the effect of financial leverage, dividend policy, profitability, firm size, and liquidity on firm value in pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange. The population in this study were all pharmaceutical companies listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique utilized the purposive sampling method and obtained 7 companies. This study utilized multiple regression analysis. The results show that partially financial leverage and profitability variables have an effect on firm value, meanwhile dividend policy, firm size and liquidity variables don’t have effect on firm value. Simultaneously the variables of financial leverage, dividend policy, profitability, firm size and liquidity have an effect on firm value. This research is expected to provide benefits for the pharmaceutical sub-sector.